The Influence of Compensation, Competence, and Work Environment on Employee Performance at PT. Indo Graha Utama with Job Satisfaction as a Mediating Variable - Purwadi, Didik; Ahmad, Gofur; Haryoto, Cecep Yoto (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This study aims to determine the effect of compensation, competence, and work environment on employee performance with job satisfaction as a mediating variable at PT. Indo Graha Utama. The research method used is quantitative with an associative research design. Data were collected through a questionnaire distributed to 200 respondents working at PT. Indo Graha Utama. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (SmartPLS). The results of the study indicate that compensation, competence, and work environment have a positive and significant effect on job satisfaction and employee performance. Job satisfaction also has a positive and significant effect on employee performance. Additionally, job satisfaction mediates the influence of compensation, competence, and work environment on employee performance. Thus, this study contributes to the understanding of the role of job satisfaction in mediating the influence of organizational factors on employee performance. The results of this study can be used as a reference for improving employee performance through enhancing job satisfaction.